CLOSED CASES? â€“ THE MENTIONING OF MEDICAL ERRORS IN DOCTORSâ€™ MEMOIRS - Potempa, Angelika (European Scientific Journal, ESJ, 2015)
The concession of errors in the pursuit of the art of medicine, where mishaps can lead to deleterious consequences is at the center of this paper. The social costs of medical errors and a professional culture with a strong tradition of self-regulation and shielding itself via a more or less permeable â€œWall of Silenceâ€ make the issue not only interesting but keep it timely. The focus is on how and within what framework medical errors are admitted in the memoirs of American doctors. The times remembered reach from the 1950s and 1960s to the present.